Chemically modified sugarcane bagasse as a potentially low-cost biosorbent for dye removal - Saiful Azhar, Saad; Khairuddin, Md. Isa; Rohazita, Bahari (Elsevier B. V., 2010)
Link to publisher’s homepage at http://www.elsevier.com/